Assessment of Uterine and Umbilical Artery Haemodynamics at Different Stages of Gestation in Goats - Gnanavelou, Shalini; Aravind, Amritha; Choppillil, Jayakumar; Mooloor Harshan, Hiron; Villan Lonappan, Gleeja; Nagendra Reddy, Yakkanti (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Doppler indices of the uterine and umbilical arteries are valuable for assessing foetal viability and intrauterine growth. This study evaluated blood flow in the umbilical (UmA) and uterine arteries (UtA) during first (<50 days), second (51-100 days) and third (>101 days) stages of gestation in Attappady Black (low prolific) and Malabari (high prolific) goats. Six does per breed were assessed in each stage for Resistance Index (RI) and Pulsatility Index (PI). Both UmA and UtA indices showed a significant decline (p≤0.05) as gestation progressed. UmA PI and RI significantly decreased in third stage compared to first and second stage in both breeds; though no interbreed differences were noted. In Malabari goats, the left UtA showed significant reductions from the first to third stage (PI: 1.08 ± 0.08 to 0.80 ± 0.08; RI: 0.83 ± 0.06 to 0.63 ± 0.05), while in Attappady goats, the right UtA showed similar changes from second to third stage (PI: 1.13 ± 0.09 to 0.83 ± 0.09; RI: 0.74 ± 0.02 to 0.62 ± 0.02). No significant variation was observed in the left UtA of Attappady or the right UtA of Malabari goats. These findings highlight gestational hemodynamic changes and provide reference Doppler values for evaluating uteroplacental circulation in goats.